2022
DOI: 10.1111/ppc.13048
|View full text |Cite
|
Sign up to set email alerts
|

The effect of insight, loneliness, and hope levels on medication adherence in patients with schizophrenia

Abstract: Design and Methods: In this descriptive and analytical study, the effects of insight, loneliness, and hope levels on medication adherence in 202 patients with schizophrenia were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…There are many hypotheses to explain the increased smoking rates in schizophrenia. It has been reported that patients with schizophrenia tend to smoke more in order to reduce disease-related symptoms, alleviate the side effects of neuroleptic therapy, and/or treat cognitive deficits (self-treatment hypothesis) (2,5,6). In addition, it has been reported that smoking can be a means of coping with the feeling of boredom and loneliness caused by the loss of social and occupational functionality caused by the disease (7) and it can also help to get rid of the emotional burden and tension encountered in daily life with the stimulating or calming effect of smoking (8), also, it is emphasized that schizophrenic individuals who move away from society or do not know what they can do to establish a relationship when they enter the society can reduce this behavioral gap with smoking and that smoking is an addiction that is a socialization tool (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many hypotheses to explain the increased smoking rates in schizophrenia. It has been reported that patients with schizophrenia tend to smoke more in order to reduce disease-related symptoms, alleviate the side effects of neuroleptic therapy, and/or treat cognitive deficits (self-treatment hypothesis) (2,5,6). In addition, it has been reported that smoking can be a means of coping with the feeling of boredom and loneliness caused by the loss of social and occupational functionality caused by the disease (7) and it can also help to get rid of the emotional burden and tension encountered in daily life with the stimulating or calming effect of smoking (8), also, it is emphasized that schizophrenic individuals who move away from society or do not know what they can do to establish a relationship when they enter the society can reduce this behavioral gap with smoking and that smoking is an addiction that is a socialization tool (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The primary reason for this is that patients with schizophrenia are reluctant to seek professional help for smoking cessation (5). It has been reported that the reasons for patients' difficulty in quitting smoking are avoidance or lack of support and structured medical help in quitting smoking, lack of knowledge about withdrawal treatments, and the fear of health professionals intensifying the aggressive behavior of patients or intensifying their psychotic symptoms (5,6,11). Another reason is that even in psychiatric treatment centers where patients are treated, smoking is generally considered an accepted social activity, smoking is allowed even in areas where smoking is prohibited, and patients with schizophrenia are rarely encouraged to quit smoking (2).…”
Section: Introductionmentioning
confidence: 99%